KEMAMPUAN SISWA MENCERITAKAN PENGALAMAN MELALUI MODEL COOPERATIF INTEGREAD READING AND COMPOSITION (CIRC) - Rahman, Rahman (JURNAL PESONA, 2018)
AbstractThis study aims to determine whether Cooperative Integread Reading and Composition (CIRC) learning model can improve the studentsâ ability in telling impressive experiences. The esearcher used classroom action research design with data retrieval method on the test in the form of test. The learning model used is Cooperative Integread Reading and Composition (CIRC). Subjects in this study are the first semester students of class VII, MTs Negeri Sukoharjo academic year 2017/2018 which amounted to 34 students. From the result of data analysis, it is known that telling impressive experience in writing in cycle I obtained the average value of 72,74 and the complete student reaches 64,7% while in cycle II it is obtained the average 80,55 and student complete 100%. Thus the use of appropriate learning model such CIRC can improve students learning ability in telling the written story.Key Words: Cooperative Integread Reading and Composition (CIRC), written story.